WILL AI REPLACE HUMAN JOBS IN THE FILM PRODUCTION? - V. J., Bharathi; V., Vishnu Vardhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial Intelligence is utilized in multiple steps of film production such as script writing, Pre-production works, identifying locations, casting the actors, calculating the budget of the film, Box-office performance, Demographics of the audience, enhancing VFX, animations, CGI, music and Post-production works (Editing, colouring, sound design). This article explores the arrival of AI in film production, popular filmmaker’s and artists’ opinions on AI, how AI benefits and challenges human jobs in the Film industry, and AI which are used in every stage of filmmaking. This article elucidates about movies generated through AI, how popular movie production companies like 20th Century Fox, and Warner Bros. use AI as a tool to enhance their films, AI which are used to generate films, and jobs that AI is unlikely to replace. This article concludes by stating how humans should use AI in order to sustain in this era of AI.